Hepcidin levels, markers of iron overload, and liver damage in children with beta-thalassemia major - Sari, Indah; Sari, Dian Puspita; Damayanti, Moretta; Salwan, Hasri (Indonesian Pediatric Society, 2024)
Background Thalassemia is a hemoglobin synthesis disorder that causes patients to need lifelong blood transfusions, leading to iron overload and alter organ function, including the liver. Hepcidin, produced by the liver, plays a role in iron homeostasis and should be increased in excess iron stores. However, the level decreases in thalassemia due to some factors, such as ineffective erythropoiesis and liver damage. Recent publications revealed that hepcidin could be associated with iron overload and also a marker of liver diseases. Objective To analyse the correlation between hepcidin level, markers of iron overload, and liver damage in beta-thalassemia major. Methods This cross-sectional study included all ?-thalassemia major age 2-18 years admitted to Dr. Mohammad Hoesin Hospital, Palembang, South Sumatera, who underwent blood transfusions from March to August 2022. We measured the level of iron overload markers, hepcidin, liver function test (LFT), and performed liver ultrasonography (USG). Results Of 97 subjects, median hepcidin level was 10.01 ng/mL and 68% of the subjects showed a decrease. The iron overload parameters were evaluated from serum iron levels (P=0.13), ferritin levels (P=0.90), and transferrin saturation (P=0.29) and 24.7% had abnormal liver USG findings. Spearman’s correlation revealed that only direct bilirubin (DB) (r=0.35; P=0.001) and liver USG (r=0.20; P=0.05) had positive correlations with decreased levels of hepcidin. Also, it had 91.7% sensitivity in predicting liver damage from ultrasound. Conclusion The hepcidin level was not significantly associated with iron overload markers.